Manajemen Kurikulum dan Pembelajaran Pendidikan Inklusi di SLB SD Purba Adhi Suta Purbalingga - Evri Maulana; Naswa Khuerul Istiqomah; Rinita Putri Pratiwi; Sahra Fakhturahma (J-PGMI: Jurnal Pendidikan Guru MI, 2024)
Objektif: The aim of this research is to describe the management of the inclusive education curriculum at Purba Adhi Suta Elementary School, Purbalingga, which includes: student acceptance, objectives of implementing the curriculum, characteristics of inclusive schools, inclusive learning methods, and teacher challenges and solutions. This observation uses a qualitative descriptive method.In conclusion, the management curriculum at Purba Adhi Suta Purbalingga Elementary School includes, 1) student management. Starting with planning for new student admissions through beneficiary needs analysis activities. The implementation of accepting students with special needs through the inclusion route is carried out by referring to the registration mechanisms and requirements stated in the guidelines for implementing Purbalingga student registration. 2) curriculum management related to the development of the use of the 2013 curriculum, modified according to the abilities and conditions of students. 3) characteristics of inclusive schools that shape the independence of regular students and those with special needs. 4) learning methods that provide a platform for students to have skills in their fields, and collaborate with parents to support students. 5) challenges and solutions for teachers who still have difficulty dealing with children with special needs.